Cólica infantil: o cuidado de mães e equipes da estratégia de saúde da família - Abreu, Flávia Corrêa Porto de (2015)
Infant colic is a common clinical condition in newborns, starting the second week after birth and persisted until about the sixth week of the child's life. Is related to the immaturity of the gastrointestinal system and also known as excessive crying syndrome. The Family Health Units are privileged locations for new health promotion practices, however, the professionals of these staffs need to build with families the nursing for children with colic. This study aim to characterize the interrelation of the management of infantile colic by mothers and professionals of the Family Health Strategy, in order to broaden the humanization of care. It was adopted as a theoretical reference the Symbolic Interactionism and the methodological reference a Narrative Research. The Data collection was developed through two interview strategies: a focus group to understand the professional care and the unstructured interview of individual approach with the mothers, both with the focus on the care of colic. The integrated analysis of 31 interviews with mothers and 4 focus groups with professionals revealed five management translators themes of infantile colic: "diagnostic approach"; "Therapeutic Approach"; "Feelings"; "Support in care"; "Experts". It was identified that colic child is a complain by mothers and / or families to the Family Health Units, however the user embracement is not entire, for lack of translators elements of a human and comprehensive care from professionals. For these, colic means a physiological and self-limited event, associated with strong medicalization, supporting the results of this study. However, for mothers experiencing this situation there is suffering and in an attempt to intend the practices prescribed by professionals, they feel powerless for not achieve full relief from colic. Thus, the study indicates that changes in care practices in the Family Health Strategy is needed to change the perception of infant colic staff, justified by the frequency of this complaint in the child care everyday. There is a lack of protocols for the care of the colic, creating the feeling of insufficiency, this fact is present in the narrative of social actors from this study. Therefore, all spaces of reflection and learning about the practice of care to this event, need to change in order to obtain a humanized and comprehensive care through the acceptance of the complaint of infantile colic.